Policy Complementarities in the Promotion of Electric Vehicles - Lavan T. Burra; Stephan Sommer; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
To accelerate the electrification of the transport sector, many countries subsidize both the construction of public charging infrastructure and the purchase of electric vehicles (EVs). Possible complementarities between these measures raise the question of their optimal calibration. Drawing on county-level panel data from Germany spanning 2014–2021, this paper explores this question with an econometric model of EV uptake. Employing fixed effects- and instrumental variable estimators, we find that charging infrastructure has a positive and significant effect on the uptake, one whose magnitude increases with the subsidy level for car purchases. Simulations using the model estimates show how the predicted number of EVs for a given charging capacity level increase with higher consumer subsidies, allowing for a back-of-the-envelop calculation of the optimal expenditure of the two measures.
Keywords: H23; L91; Q58; 330; Electric vehicles; charging capacity; consumer subsidy; calibration